Primary Abscess of Psoas a Klebsiella Gas-producing pneumoniae - Lyford-Pike, Patrick; Le Pera, Roberto; Rodríguez, A.; Andreoli, Gustavo; Vila, A.; Veirano, Gustavo (Cirugía del Uruguay, 2006)
This clinical case refers to a primary abscess of psoas to Klebsiella pneumoniae with evolutive mediastinal involvement, in a Diabetic female patient aged 61. There is a revision of literature. It is difficult to make an early diagnosis given the inespecificity of clinical symptomatology. CAT scan proved to be the study with the best cost-benefit ratio. Treatment is based on two pillars, antibiotic therapy and surgical drainage